Corrections to “Effects of Targeted Assistance and Perturbations on the Relationship Between Pelvis Motion and Step Width in People With Chronic Stroke” - Nicholas K. Reimold; Holly A. Knapp; Alyssa N. Chesnutt; Alexa Agne; Jesse C. Dean (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Presents corrections to the paper, (Corrections to “Effects of Targeted Assistance and Perturbations on the Relationship Between Pelvis Motion and Step Width in People With Chronic Stroke”).